Plants of Healing: The lasting impact of Arab contributions to herbal medicine - Garuba, Taofeeq; Kankawi, Uthman Idrees; Abdulbaki, Abdulbaki; Adeyemi, Sherif Babatunde; Ola Yusuf, Babalola; Sabiu, Saheed (Ethnobotany Research and Applications, 2025)
Background: The Arab world has historically served as a major center for the collection, documentation, and application of traditional medicinal practices. During the Islamic Golden Age, Arabian scholars not only preserved Greco-Roman medicinal knowledge but also advanced herbal medicine through empirical investigations and the synthesis of diverse cultural practices. Here, we appraised the enduring contributions of Arabian herbal medicine from the Islamic Golden Age to modern pharmacology, with particular attention to specific medicinal plants and their documented therapeutic applications across various diseases. Methods: This review employed a historical-analytical method, sourcing classical texts, peer-reviewed scientific literature, and ethnobotanical surveys to identify influential Arab scholars, medicinal plant usage, and their ethnopharmacological relevance. Medicinal plants discussed were selected based on documentation in Arab literature and modern pharmacological studies. Results: Arab scholars such as Avicenna, Al-Razi, and Ibn Al-Baytar made pioneering contributions to pharmacology, distinguishing it from general medicine. Over 1400 plant species were documented in Arab pharmacopoeias, many of which have shown efficacy in managing diabetes, hypertension, liver and kidney disorders, skin conditions, and neurological diseases. Their traditional use correlates with contemporary pharmacological findings, substantiating their therapeutic values. Conclusions: Arab contributions to herbal medicine were foundational in the development of systematic pharmacology and influenced both Eastern and Western medical traditions. Recognizing and preserving this knowledge is essential for its integration into modern healthcare and for guiding future drug discovery and development, particularly through interdisciplinary approaches leveraging traditional wisdom and modern technology. Keywords: Arabians; Diseases; Medicinal plants; Modern pharmacology; Phytotherapy; Traditional practices